2016
DOI: 10.1111/jre.12386
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as a pro‐osteogenic agent in oral implantology: a systematic review of histomorphometric outcomes in animals and quality evaluation using ARRIVE guidelines

Abstract: The aim of this review was to evaluate the outcomes of preclinical trials that assessed the use of melatonin as a pro-osteogenic agent in the field of oral implantology. Melatonin is a hormone that has been shown to have beneficial antioxidant and bone-metabolic effects. A number of experimental studies have analysed its effect in promoting osseointegration around dental implants in animals. A bibliographic search in PubMed, Scopus and EBSCOhost was performed. Animal studies that quantitatively analysed the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…The antioxidant effects of melatonin have been reported in humans and laboratory animals in clinical and experimental studies [1, 15, 19, 21, 28, 29]. Other effects of melatonin, such as its anti-inflammatory [23, 30], antioxidant and anti-inflammatory [31], and pro-osteogenic agent [32] effects, have been studied in dogs. A significant increase in plasma lipid peroxide (LPO) level, nitrite and nitrate (NOx) level, and erythrocyte oxidized glutathione/reduced glutathione (GSSG/GSH) ratio has been reported following the removal of the premolars and molars in dogs whereas melatonin treatment at the time of surgery has been shown to restore the normal values of these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant effects of melatonin have been reported in humans and laboratory animals in clinical and experimental studies [1, 15, 19, 21, 28, 29]. Other effects of melatonin, such as its anti-inflammatory [23, 30], antioxidant and anti-inflammatory [31], and pro-osteogenic agent [32] effects, have been studied in dogs. A significant increase in plasma lipid peroxide (LPO) level, nitrite and nitrate (NOx) level, and erythrocyte oxidized glutathione/reduced glutathione (GSSG/GSH) ratio has been reported following the removal of the premolars and molars in dogs whereas melatonin treatment at the time of surgery has been shown to restore the normal values of these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…A melatonina tem mostrado efeitos benéficos antioxidantes e sobre o metabolismo ósseo (ARORA e IVANOVSKY, 2017) 18 . A melatonina que se apresenta diminuída em distúrbios do sono tem ação na maturação e na remodelação de tecidos de sustentação, agindo na expressão gênica dos odontoblastos 16 . A duração inadequada do sono ou a ineficiência dele estão associadas a baixa da vitamina D em homens adultos.…”
Section: Discussionunclassified
“…Regarding the quality assessment of studies, most of the categories were classified as excellent or average. A previous systematic review [54] using the ARRIVE guidelines reported that most animal studies lack a clear indication of the reasons for choosing a particular animal model, contributing to a lower score for this item. This item also received the lowest score.…”
Section: Discussionmentioning
confidence: 99%
“…This item also received the lowest score. This aspect is considered an important criterion for preclinical animal trials [54]. Thus, even if it is already well-known that some results of studies in rodents can be extrapolated to humans, it is important to highlight the relevance of the model used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation